2020
DOI: 10.7717/peerj.8528
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effect of a high-salt diet on transcriptome dynamics in rat hypothalamic forebrain and brainstem cardiovascular control centers

Abstract: Background High dietary salt intake is strongly correlated with cardiovascular (CV) diseases and it is regarded as a major risk factor associated with the pathogenesis of hypertension. The CV control centres in the brainstem (the nucleus tractus solitarii (NTS) and the rostral ventrolateral medulla (RVLM)) and hypothalamic forebrain (the subfornical organ, SFO; the supraoptic nucleus, SON and the paraventricular nucleus, PVN) have critical roles in regulating CV autonomic motor outflows, and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 145 publications
(140 reference statements)
1
9
1
Order By: Relevance
“…Studies have shown that many cardiovascular diseases, such as MI, HF and hypertension, are characterized by reduced cardiac function due to peripheral inflammation associated with increased central sympathetic tone, while neuroinflammation of the PVN in turn leads to increased central sympathetic tone 4 . Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output 24,25 . In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that many cardiovascular diseases, such as MI, HF and hypertension, are characterized by reduced cardiac function due to peripheral inflammation associated with increased central sympathetic tone, while neuroinflammation of the PVN in turn leads to increased central sympathetic tone 4 . Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output 24,25 . In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“… 4 Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output. 24 , 25 In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation. 26 , 27 We performed a study on the role of TLR4 in the mechanism of PVN‐mediated sympathetic activation after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the approach we used here to anchor micropunched regions to atlas-mapped areas of the brain allows for important linkages between gene expression changes and neural substrates implicated in not only autonomic functions but in the regulation of food intake and body weight. A few studies have reported “bulk” or single-cell transcriptomic surveys for brainstem regions implicated in these functions, including (in addition to the RVLM) the area postrema and/or the nucleus of the solitary tract (see, e.g., in rats: Liberini et al, 2016; Ramachandran et al, 2020; in mice: Dowsett et al, 2021). However, these studies have not linked their microdissected regions to precise locations in an atlas reference space.…”
Section: Discussionmentioning
confidence: 99%
“…First, Pawar et al (2017 and2018) used a two-fold change in gene expression as the threshold for detecting differences between aged vs. young RVLM and it is possible that there might be gene expression differences that are less than two-fold in magnitude. In fact, several studies have used the combination of less than two-fold difference with statistical significance as a framework to establish changes in gene expression (Peart et al, 2005;Raouf et al, 2008). Second, a potential effect of aging on GABA and glutamate neurotransmission-related gene expression in the RVLM of middle-aged F344 rats was not explored.…”
Section: Introductionmentioning
confidence: 99%